Alterations in host DNA methylation in response to constitutive expression of Hop stunt viroid RNA in Nicotiana benthamiana plants. (6th March 2015) - Castellano, M.; Martinez, G.; Pallás, V.; Gómez, G.
Abstract : Increasing evidence points to the epigenetic regulation of transcriptional activity as a general mechanism controlling host response to pathogen infection. Recent results revealed that cucumber plants infected with Hop stunt viroid (HSVd) showed alterations in the DNA methylation pattern of usually silenced rRNA genes that are consequently transcriptionally reactivated during infection. These results indicated that, at least in cucumber, HSVd pathogenesis could be associated with disruptions in the transcriptional mechanisms regulated by epigenetic modifications of host DNA. To determine if this disorder in host regulatory activity could be a common phenomenon that occurs in other viroid–host combinations, here, the transcriptional activity in transgenic Nicotiana benthamiana constitutively expressing HSVd (HSVd/Nb) was analysed. It was observed that the HSVd RNA accumulation in N. benthamiana mimics the alteration induced by viroid infection in cucumber, promoting the accumulation of ribosomal‐derived small RNAs (rb‐sRNAs). Bisulphite sequencing demonstrated that this phenomenon was linked to a loss of symmetric cytosine methylation and correlated with an increasing accumulation of rRNA precursors in HSVd/Nb plants. The data supports the hypothesis that the interference of this pathogenic long noncoding RNA (lncRNA) in epigenetic mechanisms (associated to rDNA methylation) controlling plant gene expression is not restricted to a specific host. Thus, this phenomenon may be more general and able to occur in other viroid–plant interactions.